Reconversión productiva como política de desarrollo agropecuario dirigida a la producción campesina en el marco de los procesos de apertura económica en Costa Rica (1996-2000) - Porras Solís, Ángel Jesús (Revista de historia., 2018)
The article addresses the context in which the Productive Reconversion Program of the Agricultural Sector arises in the late 1990s, as a response to the demands of the peasant groups for an agricultural development policy that implies the productive transformation and the competitive incursion in domestic and foreign markets. It examines the main implications of economic opening processes on peasant production, as well as the process of negotiation, approval and shaping of the program. Finally, an overview of the first projects of productive reconversion approved with resources of the program is presented.